EXPLORING THE RELATIONSHIP BETWEEN CYSTATIN C LEVELS AND GLYCATED HEMOGLOBIN IN DIABETIC NEPHROPATHY PATIENTS - Miraxmedova Xilola To‘xtasinovna,; Botirova Nigina Akram qizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Diabetic nephropathy (DN) is a severe complication of diabetes mellitus, characterized by progressive kidney damage due to prolonged hyperglycemia. Early detection and monitoring of kidney function are crucial for managing DN and preventing further renal deterioration. Traditionally, serum creatinine has been used to assess renal function; however, it has limitations, particularly in detecting early stages of kidney dysfunction.Cystatin C has emerged as a promising biomarker for more accurately assessing glomerular filtration rate (GFR) and overall renal function, as it is less influenced by muscle mass and other factors that affect creatinine levels. Additionally, cystatin C1 has been found to correlate with diabetic complications, making it a relevant marker in DN.This study aimed to explore the relationship between cystatin C levels and glycated hemoglobin (HbA1c) in diabetic nephropathy patients, with a focus on patients categorized based on their GFR, calculated using a combined creatinine-cystatin C formula.